Birth and mortality of maned wolves Chrysocyon brachyurus (Illiger, 1811) in captivity - MAIA O. B. (Brazilian Journal of Biology, 2002)
The aims of this study were to verify the distribution of births of captive maned wolves Chrysocyon brachyurus and the causes of their deaths during the period from 1980 to 1998, based on the registry of births and deaths in the International Studbook for Maned Wolves. To determine birth distribution and average litter size, 361 parturitions were analyzed for the 1989-98 period. To analyze causes of mortality, the animals were divided into four groups: 1. pups born in captivity that died prior to one year of age; 2. animals born in captivity that died at more than one year of age; 3. animals captured in the wild that died at any age; and 4. all animals that died during the 1980-98 period. In group 1, the main causes of mortality were parental incompetence (67%), infectious diseases, (9%) and digestive system disorders (5%). The average mortality rate for pups was 56%. Parental incompetence was responsible for 95% of pup deaths during the first week of life. In group 2, the main causes were euthanasia (18%) and disorders of the genitourinary (10%) and digestive systems (8%). Euthanasia was implemented due to senility, congenital disorders, degenerative diseases, and trauma. In group 3, the main causes were digestive system disorders (12%), infectious diseases (10%), and lesions or accidents (10%). The main causes of mortality of maned wolves in captivity (group 4) were parental incompetence (38%), infectious diseases (9%), and digestive system disorders (7%).